Using Pill Identification Calls to Poison Centers as a Marker of Drug Abuse at Three Texas Military Bases. Issue 11 (November 2017) - Ng, Patrick C.; Maddry, Joseph K.; Sessions, Daniel; Borys, Douglas J.; Bebarta, Vikhyat S.
Abstract : Objectives: Opioid abuse is a growing problem in civilian communities, and it has developed in the military as well. Telephone calls to poison centers requesting pill identification (ID) is a marker of drug abuse. This study identifies the number of pill ID calls made to the poison centers from areas containing and surrounding three Texas military bases during an 8-year period. Methods: We performed a retrospective observational study identifying calls to certified poison centers in Texas from 2002 to 2009 that identified hydrocodone tablets and other pain medications. We noted the calls made from ZIP codes containing and surrounding the three largest military bases in Texas. Results: We reviewed 75, 537 drug ID calls for any drug from the ZIP codes of interest. Total drug ID calls increased 105% and the number of calls for hydrocodone increased 463%. Conclusions: In our study most of the drug ID calls from military communities in Texas were for hydrocodone. The rate of calls for hydrocodone increased more than the rate of calls for other analgesics from 2002 to 2009. Using drug ID calls as a surrogate of drug abuse, our results suggest that hydrocodone abuse has increased within military communities and that poison center data can be a reliable surrogate for prescription drug abuse near military bases. Future studies are needed to further understand the extent of this problem in military and civilian communities. We can use this information to heighten awareness, influence prescription practices, establish practice guidelines, and develop educational programs to mitigate the increasing rate of prescription analgesic abuse in the United States. Abstract : Prescription opioid abuse is a growing problem in civilian communities, and such abuse has developed within the military community as well. Using telephone calls to poison centers requesting pill identification as a marker of drug abuse, we found that from 2002 through 2009, opioid abuse, particularly hydrocodone abuse, increased in the communities surrounding and including three military bases in Texas.